To determine whether the given points \((0, 2)\) and \((0, -4)\) are solutions to the system of equations \(y = 2x + 2\) and \(y = 2x - 4\), we will substitute the x-coordinates of the points into each equation and see if the corresponding y-values are satisfied.
-
For the point \((0, 2)\):
-
Substitute \(x = 0\) into the first equation \(y = 2x + 2\): \[ y = 2(0) + 2 = 2 \] So, the point \((0, 2)\) satisfies the first equation.
-
Now substitute \(x = 0\) into the second equation \(y = 2x - 4\): \[ y = 2(0) - 4 = -4 \] The point \((0, 2)\) does not satisfy the second equation.
-
-
For the point \((0, -4)\):
-
Substitute \(x = 0\) into the first equation \(y = 2x + 2\): \[ y = 2(0) + 2 = 2 \] The point \((0, -4)\) does not satisfy the first equation.
-
Now substitute \(x = 0\) into the second equation \(y = 2x - 4\): \[ y = 2(0) - 4 = -4 \] So, the point \((0, -4)\) satisfies the second equation.
-
Since neither point satisfies both equations simultaneously, we conclude:
Neither of these points are solutions.